Methylphenidate for Attention-Deficit and Hyperactivity Disorder in Adult Patients With Substance Use Disorders: Good Clinical Practice - Chamakalayil, Sunsha; Strasser, Johannes; Vogel, Marc; Brand, Serge; Walter, Marc; Dürsteler, Kenneth M. (Frontiers in Psychiatry, 2021)
Attention-deficit and hyperactivity disorder (ADHD) is one of the most widespread neurodevelopmental disorders in children and adolescents, and in majority of them, it persists into adulthood. ADHD and substance use disorder (SUD) commonly co-occur in clinical adult population. The higher than normal prevalence rates of SUDs in people with ADHD indicate an increased risk for developing SUD. This narrative review deals with the question whether or not adults with both disorders should be treated with methylphenidate (MPH), addressing specific issues surrounding this form of treatment. MPH is considered as first-line pharmacotherapy for ADHD. However, because of its stimulant-like reinforcing properties, MPH has a significant misuse potential to which persons with SUDs are especially susceptible. Appropriate treatment is therefore complex because of concerns about misuse and diversion of MPH medication. As a result, clinicians may be reluctant to use MPH to manage ADHD symptoms in these patients. However, it is essential to diagnose and treat ADHD adequately since appropriate therapy reduces the impairments as well as the risk of developing comorbid disorders and poor treatment response. MPH should not be deprived from these patients due to the risk for misuse; especially since several strategies can be applied to minimize the risk. To conclude, carefully applied guideline-based diagnostics to clarify the potential presence of ADHD as well as a responsible prescription practice in a well-defined therapeutic setting with reliable monitoring of medication intake and regular consultations are essential conditions for a safe and proficient MPH treatment of ADHD in patients with SUD.